Dose-dependent lipid peroxidation induction on ex vivo intestine tracts exposed to chyme samples from fumonisins contaminated corn samples. Issue 5 (August 2015) - Garbetta, A.; Debellis, L.; De Girolamo, A.; Schena, R.; Visconti, A.; Minervini, F.
Highlights Fumonisins induced lipid peroxidation after short intestinal exposure. Digestion process influences the lipid peroxidation induced by fumonisins. The peroxidation induction is related to fumonisins concentrations.